2013
DOI: 10.1007/s13205-013-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer potential of flavonoids: recent trends and future perspectives

Abstract: Cancer is a major public health concern in both developed and developing countries. Several plant-derived anti-cancer agents including taxol, vinblastine, vincristine, the campothecin derivatives, topotecan, irinotecan and etoposide are in clinical use all over the world. Other promising anti-cancer agents include flavopiridol, roscovitine, combretastatin A-4, betulinic acid and silvestrol. From this list one can well imagine the predominance of polyphenols, flavonoids and their synthetic analogs in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
265
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(299 citation statements)
references
References 233 publications
8
265
0
5
Order By: Relevance
“…[15,16] GC-MS analysis of ethanol and petroleum ether led to the identification of phytoconstituents which was confirmed based on the molecular weight (MW), molecular formula (MW), peak area and retention time (RT) ( Table 2). The spectrum profile confirmed the presence of number of phyto compounds in ethanol extract of C.pictus leaves (Fig 1) …”
Section: Resultsmentioning
confidence: 94%
“…[15,16] GC-MS analysis of ethanol and petroleum ether led to the identification of phytoconstituents which was confirmed based on the molecular weight (MW), molecular formula (MW), peak area and retention time (RT) ( Table 2). The spectrum profile confirmed the presence of number of phyto compounds in ethanol extract of C.pictus leaves (Fig 1) …”
Section: Resultsmentioning
confidence: 94%
“…Several studies revealed flavonoids as potential antiproliferative and antioxidant agents (Batra andSharma 2013, Weng andYen 2012). Since a previous study with the ethyl acetate extract of M. floribunda leaves reported the flavonoid myricetin-3-galoctoside as one of the main compounds (Tietbohl 2012), this prompted us to determine the total phenolic, flavonoid and tannin contents and the antioxidant capacity of M. floribunda leaves in order to correlate chemical composition with antiproliferative effect.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical assays of the extract revealed a high amount of total phenolic compounds, tannin (13%) and flavonoids (24%). Therefore, it is possible to assert that antioxidant capacity and antiproliferative activity of the extract are in suitable correlation with the chemical compound contents (total phenolic compounds, tannin and flavonoids), once these classes of compounds are known as potent antioxidants and anticancer agents (Einbond et al 2004, Batra and Sharma 2013, Weng and Yen 2012, Wang et al 1997. Moreover, Tietbohl (2012) reported that the main constituent of the ethyl acetate extract of M. floribunda leaves is myricetin-3-galoctoside, which has showed an antitumor-promoting activity, and could be related to the results observed in this study (Gao et al 2002, Hayder et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By virtue of their antioxidant and free radical scavenging activity, polyphenols have received much interest from researchers seeking to develop anticancer, antiangiogenic and cardiovascular-disease medications [9].…”
Section: Introductionmentioning
confidence: 99%